2014
DOI: 10.1002/em.21873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of docosahexaenoic acid and furan fatty acids on cytokinesis block micronucleus cytome assay biomarkers in astrocytoma cell lines under conditions of oxidative stress

Abstract: Fatty acids from fish such as docosahexaenoic acid (DHA) are associated with improved brain function, whereas furan fatty acids (FFAs) also found in fish oil at low levels (1%) are thought to have antioxidant properties. Understanding their effects in astrocytes is important as these cells are responsible for maintaining healthy neurons via lipid homeostasis and distribution within the brain, and their decline with aging is a possible cause of dementia. We investigated the cytotoxic and genotoxic effects of DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…For instance, in hepatocellular carcinoma, the presence of oxidative stress and inflammation leads to epigenetic instability that modifies the methylation status of DNA at different genetic loci, including tumor suppressor gene promoters, repetitive elements, and satellite DNA (84), which provides a probable link between metabolic status and the initiation of CIN. It has also been shown that under oxidative stress conditions, the addition of 1-10 mg DHA/mL to astrocyte cell culture (APOE 33/33 and 32/34 genotypes) was able to protect against H 2 O 2 genotoxic damage by decreasing the occurrence of miconuclei (85). Moreover, protein-energy malnutrition has been found to induce chromosomal aberrations (86)(87)(88), and this phenotype was rescued by ZnSO 4 supplementation (87).…”
Section: Environmental Signals and Centromeric Chromatin Instabilitymentioning
confidence: 99%
“…For instance, in hepatocellular carcinoma, the presence of oxidative stress and inflammation leads to epigenetic instability that modifies the methylation status of DNA at different genetic loci, including tumor suppressor gene promoters, repetitive elements, and satellite DNA (84), which provides a probable link between metabolic status and the initiation of CIN. It has also been shown that under oxidative stress conditions, the addition of 1-10 mg DHA/mL to astrocyte cell culture (APOE 33/33 and 32/34 genotypes) was able to protect against H 2 O 2 genotoxic damage by decreasing the occurrence of miconuclei (85). Moreover, protein-energy malnutrition has been found to induce chromosomal aberrations (86)(87)(88), and this phenotype was rescued by ZnSO 4 supplementation (87).…”
Section: Environmental Signals and Centromeric Chromatin Instabilitymentioning
confidence: 99%
“…The present study demonstrated that the NUBD frequency after treatment with the MB extract in combination with DXR in a simultaneous experimental protocol in normal and tumor cells was higher compared to the control cells. One mechanism involved in NUBDs formation is gene amplification (Fenech et al, 2011) and/or removal of DNA repair complexes (Chua et al, 2014). Our results cannot identify which gene is amplified, but one hypothesis is that the overexpression of different genes may be related to increases in the NUBDs frequency, including CCND1 that had its expression increased approximately five-fold in both cell lines.…”
Section: Discussionmentioning
confidence: 70%
“…Evaluation of the oxidant activity using the CM-H 2 DCFA probe showed an oxidant effect of the MB extract only on tumor cells, which may be related to the mutagenic effect observed in these cells. Chua et al (2014) also demonstrated that the frequency of NUBDs increased with the oxidative stress induced by H 2 O 2 in an astrocytoma cell line. Antimutagenic effects were observed in both cell lines in the CBMN-cyt assays when the cells were treated with the MB extract plus DXR.…”
Section: Discussionmentioning
confidence: 78%